Kaurenoic acid is a potent inhibitor of SARS-CoV-2 RNA synthesis, virion assembly, and release in vitro - Santos, Igor Andrade; Grosche, Victoria Riquena; Cassani, Natasha Marques; Veneziani, Rodrigo Cássio Sola; Ribeiro, Gustavo Lima; Bastos, Jairo Kenupp; Nicolau-Junior, Nilson; Merits, Andres; Martins, Carlos Henrique Gomes; Harris, Mark; Jardim, Ana Carolina Gomes (Frontiers in Microbiology, 2025)
IntroductionSevere acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is responsible for the coronavirus disease 2019 (COVID-19) pandemic, continues to pose global health challenges despite the availability of approved vaccines and antiviral drugs. The emergence of new variants of SARS-CoV-2 and ongoing post-COVID complications necessitate continuous exploration of effective treatments. Kaurenoic acid (KA) is a tetracyclic diterpenoid isolated from plants of the Copaifera genus and has been previously recognized for its anti-inflammatory, antibacterial, antifungal, and antitumor properties. However, there is a lack of knowledge about the in vitro effects of KA on viruses. Here, we evaluated its effect on SARS-CoV-2 replication for the first time.Methods and ResultsKA demonstrated a high selective index of 16.1 against SARS-CoV-2 and robust effectiveness against the B.1.617.2 (Delta) and BA.2 (Omicron) variants. Mechanistically, KA was shown to impair the post-entry steps of viral replication. In a subgenomic replicon system, we observed a decrease in viral RNA synthesis in different cell lines. Using an infectious virus, a larger reduction in the release of SARS-CoV-2 virions was observed. We suggest that KA interacts with SARS-CoV-2 proteases through molecular docking.ConclusionIn conclusion, KA emerges as an inhibitor of SARS-CoV-2 proteases and, consequently, its replication cycle. It could be a good candidate for further investigation in clinical assays against SARS-CoV-2 infection.